Mekanisme Pengelolaan Barang Bukti Narkoba Agar Tidak Mengalami Penyusutan Pada Saat Sidang Dipengadilan - Simanullang, Witriana; Manullang, Herlina (Innovative: Journal Of Social Science Research, 2024)
Drug evidence management is an important part of the law enforcement process, as it aims to maintain the authenticity and integrity of the evidence. In this context, things like improper handling, inadequate storage, and the risk of loss or damage to evidence during the trial process are common causes of evidence shrinkage. The purpose of this study is to determine how the mechanism for managing drug evidence so that it does not shrink during the trial in court and what challenges are faced in managing drug evidence that can cause shrinkage, and how to solve them. The type of research used is normative research that examines the concept of law and legislation in Indonesia. how to solve them. The type of research used is normative research that examines the concept of law and legislation in Indonesian. The data used are secondary data, consisting of primary, secondary and tertiary legal materials. The methods used in this study include literature studies, interviews with authorities, and analysis of existing policies. Research shows that effective management requires a strict documentation system, intense supervision, and training for employees working in the management of evidence. Establishment of clear standard operating procedures (SOPs), increased collaboration between agencies, and use of information technology for tracking evidence. Based on the results of this study, it can be concluded that by using this method, the management of drug evidence is expected to be maintained and not damaged during the trial. In addition, with better regulation, drug evidence can be maintained properly until the trial stage. The result will be better law enforcement and better justice.